Linear domain interactome and biological function of anterior gradient 2 - Lawrence, Melanie Laura Alexandra (The University of Edinburgh, 2013)
The Anterior Gradient 2 (AGR2) protein has been implicated in a variety of biological systems linked to cancer and metastasis, tamoxifen-induced drug resistance, pro-inflammatory diseases like IBD and asthma, and limb regeneration. The molecular mechanisms by which AGR2 mediates these various phenotypes in disease progression in both cancer and IBD are poorly understood, as is the biological function(s) of AGR2 under non-disease conditions. Here, we use a combination of biochemical techniques, organ culture, cell biology and mouse genetics to investigate the biological significance of AGR2 both in cell lines and in vivo. We present data based on phage-peptide inter-actomics screens suggesting a role for AGR2 in mediating the maturation and trafficking of a class of membrane and secretory proteins, and investigate a putative interaction between AGR2 and one member of this class of proteins. We also describe the construction of a universal vector for use in making a variety of transgenic animals, and then present data showing its use as a promoter reporter, and attempt to investigate the temporal and spatial expression of AGR2 in the developing and adult mouse. Further, we present data describing the localisation pattern of AGR2 in the developing murine kidney using a combination of organ culture and antibody staining, and suggest a role for AGR2 in the developing kidney based on this data that is in agreement with a chaperone function for membrane and secretory proteins. Together, these data suggest that AGR2 has an intrinsic consensus docking site for a subset of its client proteins, that AGR2 plays a role in protein maturation in ciliated cell types, and provides a novel biological model to dissect the role of AGR2 in ER-trafficking.
Keywords: AGR2; Anterior Gradient 2; linear peptide; Meckelin; MKS3; BAC transgenics